Self-Assembled Peptide Habitats to Model Tumor Metastasis - Noora Al Balushi; Mitchell Boyd-Moss; Rasika M. Samarasinghe; Aaqil Rifai; Stephanie J. Franks; Kate Firipis; Benjamin M. Long; Ian A. Darby; David R. Nisbet; Dodie Pouniotis; Richard J. Williams (Gels, 2022)
Metastatic tumours are complex ecosystems; a community of multiple cell types, including cancerous cells, fibroblasts, and immune cells that exist within a supportive and specific microenvironment. The interplay of these cells, together with tissue specific chemical, structural and temporal signals within a three-dimensional (3D) habitat, direct tumour cell behavior, a subtlety that can be easily lost in 2D tissue culture. Here, we investigate a significantly improved tool, consisting of a novel matrix of functionally programmed peptide sequences, self-assembled into a scaffold to enable the growth and the migration of multicellular lung tumour spheroids, as proof-of-concept. This 3D functional model aims to mimic the biological, chemical, and contextual cues of an in vivo tumor more closely than a typically used, unstructured hydrogel, allowing spatial and temporal activity modelling. This approach shows promise as a cancer model, enhancing current understandings of how tumours progress and spread over time within their microenvironment.